Petroleum fluid components that naturally formed - A. Manan, Muhammad; Othman, Ariff; Ismail, Issham; Ikhsan, Azman (Penerbit UTM, 1997)
This book was translated from English to Malay. The early section of Chapter 1 describes the gas composition from gas wells and from oil wells. Other topics covered are phase behaviour, equation of state, etc.